Pengaruh revolusi besar dunia terhadap umat manusia - Fauzi, M Ilman (Maliki Interdisciplinary Journal, 2024)
The Industrial Revolution was a revolution that occurred in England and practically changed the world economy which initially only relied on simple agriculture and industry were replaced by large-scale industries by relying on modern machines and equipment that encourages modernization in civilization and human life. The Bolshevik Revolution is one of the most influential revolutions in civilization world. The events that took place in Russia which were initiated by Lenin gave birth to one of the political ideologies and social world as opposed to liberalism, communism. With the birth of this understanding, resulted in a cold war, the splitting of several countries in the world to change the world map who had become bipolar. The French Revolution is a revolution that occurred in 1498 marking the birth of democratic government. Events that led to the end of the monarchy in the country this wine producer also inspired the birth of new countries including the American Revolution in 1776. In this study using a qualitative descriptive method.